2017
DOI: 10.1039/c7tc04170e
|View full text |Cite
|
Sign up to set email alerts
|

A surface-modified TiO2 nanorod array/P(VDF–HFP) dielectric capacitor with ultra high energy density and efficiency

Abstract: A surface-modified TiO2 nanorod array/P(VDF–HFP) dielectric capacitor has an ultrahigh energy density of 17.5 J cm−3 at 509 kV mm−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…Besides, the morphology of TiO 2 nanowire arrays indicates large and orderly distributed interface with polymer, contributing to the Maxwell–Wagner–Sillars (MWS) polarization, a spatial charge polarization, which refers to the higher concentration of charges on the interface between two different phases due to the difference in electric conductivity. The interface in the composite provides path along the electric field for space interface charges, and contributes to the high dielectric constant [ 34 , 35 , 36 ]. The β-phase of the P(VDF-TrFE) matrix with a higher electric dipole moment than the α-phase also contributes to the high permittivity.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the morphology of TiO 2 nanowire arrays indicates large and orderly distributed interface with polymer, contributing to the Maxwell–Wagner–Sillars (MWS) polarization, a spatial charge polarization, which refers to the higher concentration of charges on the interface between two different phases due to the difference in electric conductivity. The interface in the composite provides path along the electric field for space interface charges, and contributes to the high dielectric constant [ 34 , 35 , 36 ]. The β-phase of the P(VDF-TrFE) matrix with a higher electric dipole moment than the α-phase also contributes to the high permittivity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that one-dimensional nanofillers with large aspect ratio, such as TiO 2 6 , BaTiO 3 20 , 21 , BaSrTiO 3 22 , 23 , and SrTiO 3 24 , are more effective than the nanoparticles counterparts in improving the permittivity and energy density of the dielectric NCs. One-dimensional nanofillers with a large aspect ratio can effectively alleviate the conflict between the raise of permittivity and the decline of breakdown strength.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric capacitors with the ultrafast charging and discharging speeds, high power density and low cost are very attractive materials for the potential applications in the pulsed power electronic devices, such as radars, lasers, rail guns, and medical defibrillators [1][2][3][4][5][6][7] . However, the dielectric capacitors have lower energy density than batteries, fuel cells, and double-layer supercapacitors so this type of energy storage device is still expensive and bulky [8][9][10][11][12] .…”
mentioning
confidence: 99%
“…Due to the poor wettability between polymer and ceramics, these approaches cannot really improve the compatibility between the constituents of the composites. Although the uniformity of the polymer‐based composites can be significantly improved, the wettability between matrix and fillers does not change; additionally, it should be mentioned that both the hot‐pressing and spin‐coating are not desirable for many applications because they lead to a much more complex fabrication process . A simple fabrication process is demanded for a uniform microstructure and a better compatibility of polymer‐based composites.…”
Section: Introductionmentioning
confidence: 99%